Structural interactions of complex proteins with trehalose: mechanisms for improving the multilevel structure and functional properties of lentil-quinoa protein complexes - Mohammad Alrosan (20089263) (2024)
This study aimed to explore the impact of novel method in improving the functionality and nutritional value of lentil-quinoa protein complexes. The method involved manipulating protein interactions through pH shifting and the addition of trehalose, ultimately enhancing water solubility, digestibility, and the functionality. Fluorescence, ultraviolet, and Fourier-transform spectroscopic techniques were applied to characterize the structural and molecular properties of the trehalose-conjugated lentil-quinoa protein complexes at various concentrations. After trehalose conjugation, statistically significant alterations (p < 0.05) in the tertiary and secondary protein structures and protein conformation were observed with trehalose-conjugated lentil-quinoa protein complexes at a trehalose concentration of 5% (w/w). The water solubility and digestibility of the latter conjugate-derived lentil and quinoa complex increased from 75.1 to 80% and 75 to 80.3%, respectively. Modifications in surface properties after conjugation involved significant (p < 0.05) changes in surface charge and hydrophobicity. Overall, combining the protein complexes with trehalose enhanced the digestibility and solubility of the protein complexes and improved their physical properties. The study highlights the potential of this approach to develop more sustainable and efficient plant-based protein sources for various food and nutritional applications in the food industry. Other Information Published in: International Journal of Food Properties License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/10942912.2024.2377239